EFFECTIVENESS OF TASK-BASED LANGUAGE TEACHING (TBLT) FOR SECONDARY SCHOOL LEARNERS - Namozova Sevinch Otabek qizi; Hasanova Sevinch Hotam qizi (TADQIQOTLAR, 2026)
Abstract In recent years, the field of English Language Teaching (ELT) has undergone notable transformation due to progress in pedagogical theories, digital tools, and classroom practices. As a result, teachers today have access to a diverse range of methods designed to improve learners’ language proficiency. Among these approaches, Task-Based Language Teaching (TBLT) stands out as one of the most practical and learner-centered methodologies. This article provides an in-depth overview of the advantages TBLT offers, particularly in enhancing students’ real-life communication skills and active language use. It also discusses practical strategies and considerations for educators who wish to integrate TBLT into their lessons, ensuring more effective and engaging English language learning experiences.